PEMIKIRAN ABDUL QODIR BAFAQIH ANTARA AHLUSUNNAH DAN SYI’AH SERTA KONTRIBUSINYA TERHADAP PENDIDIKAN PESANTREN (SEBUAH STUDI KOMPARASI PEMIKIRAN ISLAM DARI TANAH JAWA) - ., Hudori (Turats, 2011)
Abdul Qadir Bafaqih role against the development of Islamic thought, especially in Central Java region can not be considered small, especially if associated with the development of Shiites in Indonesia. Therefore it is not too much what was raised by Ahmad Shafi in his research, that the Shiites understand the development in Indonesia in the twentieth century of which is inseparable from the business that was founded by Abdul Qadir bafaqih, one of the scholars who took an interest and attention large enough on the development of thought and Islamic education in Indonesia. Prior to 1974, Abdul Qadir Bafaqih has attended religious understanding and practice at the time claimed by the majority of Muslims in the environment is a familiar and Ahl al-Sunnah wal Jama practice. If observed from the travel and biography and his works, it can be concluded that the patterns of thought Abdul Qadir Bafaqih lead to the observation of religious behavior in the surrounding community, as well as the influence of Shiites who had indeed been deeply rooted as a result of education and that since the early indoctrination instilled by his father. This is of course an impact on his thinking pattern that has a tendency to separate and more or less different from the mode of thinking scholars in general, including Shiite clerics. Whatever form of thinking that has been offered by Abdul Qadir Bafaqih as already described above and apart from the concept of the Sunni - Shi'ite, is still being debated and per-bincangan in the discourse of Islamic thought, the effort of ijtihad has done commendable and at least can be used as an alternative thoughts that will enrich the intellectual heritage of Islam in Indonesia, although the ideas and thoughts that still require review and further research. On the other hand, demonstrated consistency Abdul Qadir Bafaqih Islamic thoughts and the discourse it offers, most are not going to lead to the conclusion that there is essentially no difference between Sunni - Shi'ite. Bafaqih contribution lies in Islamic boarding school education is an attempt to engage in dialogue between Sunni and Shi'ite sects so that the expected occurrence of tolerance and pluralism in Islam.